Competition for access to mates predicts female‐specific ornamentation and male investment in relative testis size. (2nd July 2020) - Murray, Rosalind L.; Herridge, Elizabeth J.; Ness, Rob W.; Wiberg, R. Axel W.; Bussière, Luc F.
Abstract: Sexually selected ornaments are highly variable and the factors that drive variation in ornament expression are not always clear. Rare instances of female‐specific ornament evolution (such as in some dance fly species) are particularly puzzling. While some evidence suggests that such rare instances represent straightforward reversals of sexual selection intensity, the distinct nature of trade‐offs between ornaments and offspring pose special constraints in females. To examine whether competition for access to mates generally favors heightened ornament expression, we built a phylogeny and conducted a comparative analysis of Empidinae dance fly taxa that display female‐specific ornaments. We show that species with more female‐biased operational sex ratios in lek‐like mating swarms have greater female ornamentation, and in taxa with more ornate females, male relative testis investment is increased. These findings support the hypothesis that ornament diversity in dance flies depends on female receptivity to mates, which is associated with contests for nutritious nuptial gifts provided by males. Moreover, our results suggest that increases in female receptivity lead to higher levels of sperm competition among males. The incidence of both heightened premating sexual selection on females and postmating selection on males contradicts assertions that sex roles are straightforwardly reversed in dance flies.